Biking to Ride: Investigating the Challenges and Barriers of Integrating Cycling with Regional Rail Transit. Issue 8 (December 2018) - Ravensbergen, Léa; Buliung, Ron; Mendonca, Meaghan; Garg, Naren
Integrating bicycling with public transport can potentially benefit cyclists and transit operators. Successfully coordinating these transport modes, however, can be a difficult task when so little is known about the social and environmental barriers to this type of multimodal travel in the North American context. Using data derived from a survey of regional train service patrons in the Greater Toronto and Hamilton regions of Ontario, Canada, this study examines the challenges faced by those who cycle to/from the train, the barriers that keep passengers from commuting to/from the train by bicycle, and the sociodemographic characteristics of those cycling—and not cycling—to/from the train. Safety concerns, worries about bicycle security, and rules restricting when bicycles are permitted on trains were among the top challenges identified by individuals currently cycling to and/or from train stations. Among those who do not cycle to or from the train, appearance and comfort were the two primary concerns. Results also indicate that certain groups were more likely to cycle to/from the train than others. Notably, a large gender gap exists, approximately two-thirds (67%) of those cycling to their local train station were male. Results from this study may inform policy makers on how to successfully, and equitably, integrate cycling with regional rail transit.